Right‐sided endocarditis: eustachian valve and coronary sinus involvement. Issue 1 (22nd August 2016) - Kumar, Kartik R.; Haider, Samran; Sood, Aditya; Mahmoud, Karim A.I.; Mostafa, Ashraf; Afonso, Luis C.; Kottam, Anupama R.
Abstract : Infective endocarditis in patients with intravenous drug use commonly involves right‐sided heart valves. Eustachian valve (EV) endocarditis is not commonly seen given the valve's infrequent presence. Involvement of the coronary sinus (CS) with endocarditis is also an unusual finding. We present a case with echocardiographic findings consistent with EV endocarditis along with CS involvement, which appropriately responded to antibiotics.